ANALISIS IDIOLEK DAN SOSIOLEK PADA AKUN MEDIA SOSIAL X @leo_edw DALAM WACANA SEHARI-HARI - Muthia Nur Rohmah; Joko Purwanto (Jurnal Riset Multidisiplin Edukasi, 2026)
This study looks at the different ways the X account @leo_edw uses language in everyday chatting. It uses a descriptive and qualitative method, where the researcher carefully watches and writes down what they see. The data comes from 22 tweets that were picked because they show interesting language use. These tweets are studied using the theory of language variation by Chaer and Agustina from 2010. The results show that the personal language style, or idiolect, of @leo_edw includes expressive and thoughtful ways of talking, personal jokes, and creative word use. The sociolect, or social language style, is seen in how they adjust their language to fit different settings like online groups, work, religion, and school. These findings show that language on social media does more than just let people talk—it also helps shape who they are as individuals and how they fit into different social groups.